Pelaksanaan Pembelajaran IPS di Kelas Berprogram Pendidikan Inklusi di SMP Negeri 31 Semarang - Pratiwi, Nor Indah; Lestari, Puji (Universitas Negeri Semarang, 2020)
SMP Negeri 31 Semarang is one of the schools that implements an inclusive education system, an education system that requires all children with disabilities to be served at the nearest school and in regular classes with their peers. Social studies subjects are one of the subjects that affect children with special needs in inclusive classes because they can help develop the potential of students to be sensitive and responsive to their environment. The method used in this research is the descriptive qualitative method. The results of this study indicate that (1) The social studies learning process in the inclusion class includes planning, implementation and evaluation according to the needs and conditions of children with special needs in each inclusive class. 2) Problems encountered by social studies teachers in implementing the learning process in the inclusive class at SMP Negeri 31 Semarang: Social studies teachers do not have special abilities in dealing with children with special needs, and there is only one special tutor available. (3) Efforts in solving problems in the form of providing motivation and constructive messages for students and relying on special supervisors.